Liver diseases in pregnancy: Liver transplantation in pregnancy - Hammoud, Ghassan M (Baishideng Publishing Group Co., Limited, 2013)
Pregnancy in patients with advanced liver disease is uncommon as most women with decompensated cirrhosis are infertile and have high rate of anovulation. However, if gestation ensued; it is very challenging and carries high risks for both the mother and the baby such as higher rates of spontaneous abortion, prematurity, pulmonary hypertension, splenic artery aneurysm rupture, postpartum hemorrhage, and a potential for life-threatening variceal hemorrhage and hepatic decompensation. In contrary, with orthotopic liver transplantation, menstruation resumes and most women of childbearing age are able to conceive, give birth and lead a better quality of life. Women with orthotopic liver transplantation seeking pregnancy should be managed carefully by a team consultation with transplant hepatologist, maternal-fetal medicine specialist and other specialists. Pregnant liver transplant recipients need to stay on immunosuppression medication to prevent allograft rejection. Furthermore, these medications need to be monitored carefully and continued throughout pregnancy to avoid potential adverse effects to mother and baby. Thus delaying pregnancy 1 to 2 years after transplantation minimizes fetal exposure to high doses of immunosuppressants. Pregnant female liver transplant patients have a high rate of cesarean delivery likely due to the high rate of prematurity in this population. Recent reports suggest that with close monitoring and multidisciplinary team approach, most female liver transplant recipient of childbearing age will lead a successful pregnancy.